P‐264: Fast‐Response FFS LC Device with Multi‐rubbing Angle for VR Applications - Chen, Shi-Rui; Choi, Wing-Kit (SID International Symposium Digest of technical papers, 2024)
In this paper, we propose new fast response FFS LC devices with virtual walls by using alternating (or multi) rubbing directions, which can be generated by using photo‐alignment. These new devices can offer much‐enhanced response‐speed compared to the conventional FFS LC device. By choosing different types of “local” LC molecular arrangements or designs (easily achievable by using photo‐alignment), we may be able to alter the virtual wall pitch length, and hence also alter the response speed and transmission of these fast response LC devices. These new designs can provide a new and alternative approach to generating virtual walls by “locally” varying the rubbing angle using photo‐alignment. These devices are attractive for VR applications where high speed operation of liquid crystal devices is required.